Exploring the neuroprotective mechanisms of Jiawei Suanzaoren decoction in depression: insights from network pharmacology and molecular docking - Ruiting Ma; Wenjing Zhang; Lixia Chen; Lijun Tong (BMC Complementary Medicine and Therapies)
Abstract Background Depression is a prevalent and debilitating neuropsychiatric disorder, often associated with neuroinflammation, oxidative stress, and neuronal apoptosis. Jiawei Suanzaoren (JWSZR), a traditional Chinese medicine (TCM) formulation, has demonstrated potential in alleviating depressive symptoms. However, its precise molecular mechanisms remain unclear. This study aims to elucidate the neuroprotective effects of JWSZR in depression using network pharmacology, molecular docking, and in vitro experimental validation. Methods Active compounds of JWSZR were identified using the TCMSP and HERB databases, and depression-related targets were retrieved from GeneCards, DisGeNET, and OMIM. A protein–protein interaction (PPI) network was constructed, followed by functional enrichment analyses, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Molecular docking was employed to predict the interactions between JWSZR's active components and key target proteins. Furthermore, in vitro experiments were performed using corticosterone (CORT)-induced PC12 cell model to validate the neuroprotective effects of JWSZR, assessing cell viability and apoptosis rates. Results Network pharmacology and molecular docking revealed that JWSZR exerts neuroprotective effects through multiple targets, including estrogen receptor ESR2, HSP90AA1, and STAT1. These targets regulate immune responses, inflammatory pathways, and cell survival. In vitro, JWSZR significantly improved cell viability and reduced apoptosis in CORT-treated PC12 cells, indicating its potential to protect against depression-related neurodegeneration. Conclusion This study provides novel insights into the neuroprotective mechanisms of JWSZR in depression, suggesting that it may act through multi-target interactions involving immune modulation and apoptosis inhibition. Graphical Abstract Multi-target neuroprotective mechanism and therapeutic potential of JWSZR in depression